The Non-Psychopath's Guide to Managing an Open Source Project: Respect your staff, learn from others, and know when to let go. - Neville-Neil, George V. (Communications of the ACM, 2021)
The article asks and answers a question on management of teams working on Open Source software project with a focus on delegation of control, managers working in a technical capacity, and emulating successful managers of Open Source software development.